"accipiendo vel compilando ab aliis": De vulgari eloquentia 1.1. Reading Dante with Dante: A contribution to Dante's theory of language. (August 2021) - Luisa Ardizzone, Maria
This article analyzes Dante's theory of language and considers at first a few fragments of Dante's Latin treatise on the vernacular, reading them in light of their ancient-medieval contexts. This reading allows part-modification of the critical discourse about Dante's theory of language. The article argues that Dante's discussion did not start in the De vulgari eloquentia, as is commonly assumed, but was at first introduced in the Vita nuova . Recent studies show that the theme of laude in the Vita nuova includes a linguistic theory and a discourse on the deep structures of language. Focussing on specific words, considering them in light of the ancient-medieval background, the article organizes a transverse reading that considers layers of Dante's discourse on language from the Vita nuova to the Commedia not yet explored and evaluated.